(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2016)
Eclipta alba is a medicinal herb belonging to the family of Asteraceae. Locally it is known as Kalokeshi and has a history of ethno-medicinal properties. The crude ethanolic extract of E. alba leaves was partitioned successively by solvents of different polarities. The crude extract along with different partitionates was evaluated for their possible antimicrobial, thrombolytic and membrane stabilizing activities. In this study, n-hexane soluble fraction (HXSF) showed 55.56% maximum activity against thrombosis in comparison with streptokinase (SK) 62.67%. For hypotonic solution- and heat-induced conditions, the n-hexane soluble fractionate (67.35 ± 0.50%) significantly inhibited the haemolysis of HRBCs by 67.35 ± 0.50% and 62.12 ± 0.69%, respectively as compared to the standard acetyl salicylic acid (77.91 ± 0.29%). The ethanol extract of the plant showed higher inhibitory action against Staphylococcus aureus, Bacillus subtilis, Proteus mirabilis and Pseudomonas fluroescens. The total flavonoid content was quite significant in ethanolic extract (142.17 ± 0.15 mg/g). Hence, the results of the present study revealed that the leaves of this traditional medicinal plant are a remedy for thrombosis, red blood cell membrane stabilization and microbial infections against some human pathogens. Dhaka Univ. J. Pharm. Sci. 14(2): 207-213, 2015 (December)